Answer:
(x, y, z) = (-2, 4, 0)
Explanation:
Solving the last equation first, we have ...
2x = -4
x = -2 . . . . . divide by 2
__
Putting this in the first equation, we can write an expression for z:
-2 +y +z = 2
z = 4 -y . . . . . . . add 2-y
__
Putting this in the second equation, we have ...
4(-2) +5y +(4 -y) = 12
-4 +4y = 12
-1 + y = 3 . . . . . divide by 4
y = 4 . . . . . . . . add 1
__
Substituting this into the equation for z, we have ...
z = 4 - 4 = 0
The solution is (x, y, z) = (-2, 4, 0).